Konsep Kreatif Video Live Streaming Ilusman 3 Medan - Sya'dian, Triadi; Alfathoni, Muhammad Ali Mursid; Purba, Rinanda; Nazarruddin, Nazarruddin (Metta : Jurnal Ilmu Multidisiplin, 2023)
This study aims to explore and analyze the application of creative concepts at the 33rd Ilusman 3 Medan reunion event in 2023. This research method involves a qualitative approach with a descriptive approach. This research also involves analysis of documentation and direct observation of the reunion event that has been carried out. The results showed that the application of creative concepts in the 33rd Ilusman 3 Medan event in 2023 contributed positively to the diversity and creativity of the event. A more memorable and satisfying experience, with more dynamic visual aspects, content presentation, and reunion atmosphere. The application of creative concepts also strengthens the emotional and nostalgic bond of participants to the alma mater or alumni group of SMA Negeri 3 Medan, which is fully supported by live streaming on Youtube and Zoom Meetings. Thus the interaction between participants becomes more in-depth and active participation in creative activities takes place. In addition, creative concepts poured both offline or on the stage and online or into live streaming also create a positive impact on the image and identity of the reunion organizers, creating an impression of professionalism and innovation towards the response of modern dynamics that lead to the development of digital technology. By utilizing creative elements. The creative elements implemented have gone through the stages of the design process and neat infrastructure design. Thus the reunion event can be more dynamic, relevant, and able to create a unique and memorable experience for the participants. The results showed that using creative aspects visually can create an evocative atmosphere during the event. In addition, the creative aspects applied in live streaming can certainly increase the attractiveness of an event.